Diuresis Renography for Differentiation of Upper Urinary Tract Dilatation From Obstruction: F+20 and F-15 Methods - Taghavi, Rahim; Ariana, Kamran; Arab, Davoud (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to evaluate diuresis renography with an intravenous injection of furosemide 20 minutes after administering the radiopharmaceutical (F+20 protocol) or 15 minutes before (F-15 protocol) in patients with upper urinary tract dilatation. Materials and Methods: Twenty-one patients with pyelocaliceal system dilatation, but not ureteral dilatation, on ultrasonography were evaluated. The patients underwent diuresis renography using the F+20 and F-15 protocols. Renal scan findings and kidney split function were recorded. Then, the patients underwent surgical or conservative treatment according to their clinical conditions and imaging results. Follow-up was done 3 and 6 months postoperatively by physical examination, intravenous urography, and diuresis renography. Results: Eleven patients (52.4%) had complete obstruction in both protocols of renography, and 5 (23.8%) had an equivocal result in the F+20 and an obstructive pattern in the F-15. These patients underwent surgical operation. In 3 patients (14.3%), both protocols demonstrated a normal urinary tract. In 2 patients (9.5%), a nonobstructive response in the F+20 and an equivocal result in the F-15 were seen. One of them underwent surgical operation because of impaired kidney function during the follow-up and 1 was treated conservatively. Overall, obstruction was found in 16 out of 21 patients (76.2%) by the F-15 protocol, while it was found in 11 (52.4%) by the F+20 protocol (P = .01). The mean kidney split function was 55.15% ± 7.82% and 54.81% ± 6.87% in F+20 and F-15 protocols, respectively (P = .45). Conclusion: Using the F-15 protocol may reduce the equivocal results of the F+20 for diuresis renography.